The Role of Resilience as Mediation in Burnout Work Environment on the Performance of RSUD Sidoarjo Employees in the Era of the Pandemic Covid 19 - Wasis Nupikso; Indasah; Katmini (Universitas STRADA Indonesia, 2024)
Background: The influence of resilience on burnout is so important for hospital staff to stay focused when providing services to patients, making researchers want to see how much influence resilience has on burnout work environment on employee performance. Purpose: To analyze the influence of the Role of Resilience as Mediation in the Burnout Work Environment on the Performance of RSUD Sidoarjo Employees in the Covid 19 Covid-pandemic era. Method: The research method used is cross-sectional analytic research. The population is 1,745 people who work at the Sidoarjo Regional General Hospital with proportional random sampling, the sample obtained is 326 employees. The measuring instrument used is a questionnaire. The data analysis used is path analysis. Results: The research results show that indirectly physical work environment variables through resilience do not significantly affect performance (0.173 > 0.163). For physical variables resilience does not significantly affect performance (0.008 > -0.022). Psychological variables through resilience do not significantly affect performance (-0.017 > -0.074). Then the behavioral variable through resilience does not significantly affect performance (-0.055 > -0.253). Conclusion: No there is a role of resilience in overcoming burnout work environment on performance. Resilience indirectly through physical, psychological, and behavior in the work environment has a significant effect on performance.